The phantom of manhattan - Forsyth, Frederick, 1938- (Los Angeles, CA : Dove Audio, 1999)
More than two decades have passed since Antoinette Giry, the mistress of the corps de ballet at the Paris Opera, rescued a hideously disfigured boy named Erik from a carnival and brought him to live in the labyrinthine cellars of the opera house. Soon thereafter, his intense, unrequited love for a beautiful chous girl set in motion a tragic string of events, forcing him to flee Paris forever. Now, as she lies dying in a convent, Madame Giry tells the untold story of the Phantom and his clandestine journey to New York City to start anew, where he would become a wealthy entrepreneur and build the glorious Manhattan Opera House.......
Compact disc.